Ethio-seed: Strengthening Ethiopia’s seed system through digital innovation. Activity Report - Adimassu, Zenebe; Tibebe, Degefie; Abera, Wuletawu; Tamene, Lulseged (2025)
Seeds are the cornerstone of agricultural productivity and food security. In Ethiopia, a country heavily reliant on agriculture, the quality and availability of seeds are critical to improving yields and climate resilience. However, the national seed sector has long struggled with challenges such as fragmented supply chains, limited access to certified seeds, poor information flow, and weak traceability. To address these issues, the Ethio-Seed platform was developed as a digital solution to modernize and strengthen Ethiopia’s formal seed system. Ethio-Seed is a national digital platform hosted by the Ministry of Agriculture (MoA), designed to enhance coordination, transparency, and efficiency across all seed value chain actors—including researchers, producers, importers, regulators, and farmers. It offers real-time data management and supports regulatory compliance, ensuring quality seeds reach farmers more reliably. The urgency for such a platform became clear during the COVID-19 pandemic, which disrupted traditional seed distribution channels. Development process of this digital platform include: i) The platform was developed through a four-phase process; ii) ideation during the CGIAR COVID-19 response (2021); iii) needs assessment through consultations with the government and scientists, iv) benchmarking and development by Addis Ababa University, and v) validation and rollout through workshops and feedback sessions. The Ethio-Seed platform is backed by Ethiopia’s legal framework, including the Seed Proclamation and Seed Regulation. MoA has also issued directives on seed certification, marketing, breeder rights, and seed imports, making use of the platform mandatory for data submission and decision-making. Dashboard Components include Seed system actors, crop & variety catalogue, seed production sites and seed stock management system to tracks local and imported seed stock, carryover, and real-time inventory data to optimize supply and avoid wastage.The system is used to compile seed demand, monitor supply, and balance distribution at national and regional levels. Only regions and suppliers submitting data via the platform are recognized in official operations. The platform supports accurate forecasting, improved traceability, and decision-making to ensure seed quality and availability. In general, the Ethio-seed platform represents a strategic innovation in Ethiopia’s seed sector, enabling efficient seed data management, regulatory enforcement, and better service delivery. Its adoption will significantly enhance agricultural productivity and resilience, contributing to national food security goals.